2017
DOI: 10.1021/acs.jafc.7b02229
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment of Acetamide in Milk, Beef, and Coffee Using Xanthydrol Derivatization and Gas Chromatography/Mass Spectrometry

Abstract: Acetamide has been classified as a possible human carcinogen, but uncertainties exist about its levels in foods. This report presents evidence that thermal decomposition of N-acetylated sugars and amino acids in heated gas chromatograph injectors contributes to artifactual acetamide in milk and beef. An alternative gas chromatography/mass spectrometry protocol based on derivatization of acetamide with 9-xanthydrol was optimized and shown to be free of artifactual acetamide formation. The protocol was validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…However, acetamide, a co-product of the AFEX treatment produced during cleavage of acetyl groups from hemicellulose (Weimer et al, 1986), is not volatile, rather it can remain with the treated biomass thereby increasing its N content (Bals et al, 2011). Acetamide has been classified as Group 2B possible human carcinogen by the International Agency for Research on Cancer (Vismeh et al, 2018) because of incidences of liver carcinoma during feeding trials in rats (Jackson and Dessau, 1961;Fleischman et al, 1980). Recent studies suggest that ruminal accumulation of acetamide from AFEX treatment is transient and certain ruminal bacteria can grow on the amide (Mor et al, 2019).…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…However, acetamide, a co-product of the AFEX treatment produced during cleavage of acetyl groups from hemicellulose (Weimer et al, 1986), is not volatile, rather it can remain with the treated biomass thereby increasing its N content (Bals et al, 2011). Acetamide has been classified as Group 2B possible human carcinogen by the International Agency for Research on Cancer (Vismeh et al, 2018) because of incidences of liver carcinoma during feeding trials in rats (Jackson and Dessau, 1961;Fleischman et al, 1980). Recent studies suggest that ruminal accumulation of acetamide from AFEX treatment is transient and certain ruminal bacteria can grow on the amide (Mor et al, 2019).…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…Acetamide has been investigated as a residue from some pesticides (WHO, 2005), as a solvent with unique properties (Zhang et al, 2012), as an impurity in the manufacture of pharmaceuticals (Snodin, 2011), and as a metabolite of drugs such as phenacetin (Hinson, 1983), metronidazole (Koch et al, 1979) and acetohydroxamic acid (Putcha et al, 1984). However, more recent findings show that acetamide is present throughout the universe from intra-stellar clouds (Hollis et al, 2006) to common foods (Vismeh et al, 2018). Earlier reports indicating that acetamide was present in milk, eggs, and meat have been recently confirmed by Vismeh et al (2018) who surveyed milk and beef samples from different states in the US.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent findings show that acetamide is present throughout the universe from intra-stellar clouds (Hollis et al, 2006) to common foods (Vismeh et al, 2018). Earlier reports indicating that acetamide was present in milk, eggs, and meat have been recently confirmed by Vismeh et al (2018) who surveyed milk and beef samples from different states in the US. Wei, 2016 reported the appearance of acetamide in the NMR spectra of roasted chicory roots which was also confirmed by Vismeh et al (2018) who reported the presence of acetamide in roasted coffee beans and instant coffee but not raw coffee beans.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection for milk and beef was determined to be 10 and 11 ng/g, respectively, and the limit of quantitation for milk and beef was determined to be 19 and 23 ng/g, respectively. 15…”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggests that acetamide can pass through the rumen wall 14 and thus may enter the bloodstream. Recently, it has been shown that acetamide is already present as a food contaminant in many foods, including milk, beef, roasted coffee, 15 and chicory root. 16…”
Section: Introductionmentioning
confidence: 99%